Issues on balancing quality with quantity of higher education: the case of Taiwan - Ru-Jer, Wang (2011)
Năm 2007: Hội thảo lần I: Giáo dục đại học – Cơ hội và thách thức trong bối cảnh toàn cầu hóa và hội nhập